THE RELATIONSHIP BETWEEN PEER SOCIAL SUPPORT AND STUDENT ENGAGEMENT IN AL-HIDAYAH HIGH SCHOOL STUDENTS MEDAN - Eva Yulina; Khairil Fauzan; Tengku Nuranasmita; Atika Mentari Nataya Nst (RADJA PUBLIKA, 2024)
The aim of this research is to determine the relationship between peer social support and student engagement. This research method is a quantitative method with a correlational approach. The population in this study was 93 students with a sample of 93 students. The sampling technique used is total sampling technique. Based on the results of the product moment correlation test above, it can be seen that the significance value of the peer social support and student engagement variables is 0.001 < 0.05. This explains that there is a significant relationship between social support from peers and student engagement in students. The Pearson correlation value obtained between peer social support and student engagement was 0.677. This explains that the variable peer social support and student engagement has a positive correlation with a strong correlation coefficient. The determinant coefficient value obtained is 0.458 or 45.8% of the influence of peer social support on student engagement. Based on the determinant coefficient value, it can be seen that the influence of peer social support on student engagement is 45.8% and the remaining 54.2% is influenced by other factors.